Functional Connectivity of the Developing Mouse Cortex. (8th September 2021) - Rahn, Rachel M; Brier, Lindsey M; Bice, Annie R; Reisman, Matthew D; Dougherty, Joseph D; Culver, Joseph P
Abstract: Cross-sectional studies have established a variety of structural, synaptic, and cell physiological changes corresponding to critical periods in cortical development. However, the emergence of functional connectivity (FC) in development has not been fully characterized, and hemodynamic-based measures are vulnerable to any neurovascular coupling changes occurring in parallel. We therefore used optical fluorescence imaging to trace longitudinal calcium FC in the awake, resting-state mouse cortex at 5 developmental timepoints beginning at postnatal day 15 (P15) and ending in early adulthood at P60. Calcium FC displayed coherent functional maps as early as P15, and FC significantly varied in connections between many regions across development, with the developmental trajectory's shape specific to the functional region. Evaluating 325 seed–seed connections, we found that there was a significant increase in FC between P15 and P22 over the majority of the cortex as well as bilateral connectivity and node degree differences in frontal, motor, and retrosplenial cortices after P22. A rebalancing of inter- and intrahemispheric FC and local-distal FC dominance was also observed during development. This longitudinal developmental calcium FC study therefore provides a resource dataset to the field and identifies periods of dynamic change which cross-sectional studies may target for examination of disease states.